2014
DOI: 10.4269/ajtmh.13-0268
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of Kato–Katz, FLOTAC, Baermann, and PCR Methods for the Detection of Light-Intensity Hookworm and Strongyloides stercoralis Infections in Tanzania

Abstract: Sensitive diagnostic tools are crucial for an accurate assessment of helminth infections in low-endemicity areas. We examined stool samples from Tanzanian individuals and compared the diagnostic accuracy of a real-time polymerase chain reaction (PCR) with the FLOTAC technique and the Kato–Katz method for hookworm and the Baermann method for Strongyloides stercoralis detection. Only FLOTAC had a higher sensitivity than the Kato–Katz method for hookworm diagnosis; the sensitivities of PCR and the Kato–Katz metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
138
3
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(150 citation statements)
references
References 51 publications
5
138
3
4
Order By: Relevance
“…In that study, the sensitivity and specificity of S. stercoralis real-time PCR were 88.9% and 92.7%, respectively, compared with the combination of Baermann/Koga agar as gold standard. 15 Knopp and others 13 reported that the sensitivity of the Baermann method for detection of S. stercoralis was significantly higher than that of real-time PCR (47.1% versus 17.4%; P < 0.001), while the specificity of the Baermann method was lower than that of real-time PCR (78.4% versus 93.9%).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In that study, the sensitivity and specificity of S. stercoralis real-time PCR were 88.9% and 92.7%, respectively, compared with the combination of Baermann/Koga agar as gold standard. 15 Knopp and others 13 reported that the sensitivity of the Baermann method for detection of S. stercoralis was significantly higher than that of real-time PCR (47.1% versus 17.4%; P < 0.001), while the specificity of the Baermann method was lower than that of real-time PCR (78.4% versus 93.9%).…”
Section: Discussionmentioning
confidence: 98%
“…8,22 PCR-based methods have shown variable sensitivity for detection of S. stercoralis in fecal samples. [10][11][12][13][14][15]18 For detection of intestinal nematodes in stool samples by PCR-based techniques, optimization of DNA isolation method is essential, because of existence of large amounts of PCR-inhibitory substances in fecal samples such as bacterial proteases, nucleases, cell debris, bile acids, and so forth, and also the presence of a thick and complex cuticle that covers the worms. 18,23,24 Repetto and others introduced an improved IH DNA extraction method based on efficient lysis of larvae and removal of inhibitors in the fecal samples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Microscopic methodologies such as examination of Kato-Katz preparations, FLOTAC, and formalin/ethyl acetate concentrates have a low yield compared to culture 9,10 . A modified formalin/ethyl acetate method proposed by Anamnart et al improved rates of detection 9 .…”
Section: Stool Microscopy and Culture Methodsmentioning
confidence: 99%
“…The majority of Strongyloides PCR publications have used a real-time method with primers and probe published by Verweij et al 19 . This has also allowed for the development of multiplexed PCR 10,30,34,38 . Some studies evaluating the diagnostic accuracy of these PCR methods have used both morphological diagnosis and detection of PCR products as their reference standards, and are not reviewed here.…”
Section: Pcrmentioning
confidence: 99%